Sensing Advancement and Health Monitoring of Transport Structures - Andrea Benedetto (MDPI AG, 2021)
Planning, design, construction, maintenance and management of transport infrastructure demand new methods and approaches to optimise utilisation of materials, energy and workforce [...]